Look Out for the Elephant! and Other Stories - Blyton, Enid; Illustrated by Pape-Ettridge, Jane (London Award Publications, 1998)
Magical tales from fairyland and beyond.
Include Illustrations
Keywords: Short stories -- Children's stories -- English fiction